Differential relations of narcissism and self‐esteem to romantic relationships: The mediating role of perception discrepancy. Issue 4 (October 2016) - Ye, Shengquan; Lam, Zando Kin Wai; Ma, Zewei; Ng, Ting Kin
Abstract : Recent research has suggested that narcissism and self‐esteem, though correlated, are qualitatively different. Little research, however, has examined narcissism and self‐esteem simultaneously to test their unique contributions. The aims of this study are twofold: to examine the unique contributions of narcissism and self‐esteem to romantic relationships, and to test the mediating role of perception discrepancy (PD) in these relationships. One hundred and three pairs of dating couples in Hong Kong were recruited to complete measures of narcissism, self‐esteem, relationship satisfaction and PD. Results from actor–partner interdependence modeling (APIM) indicate that narcissism had significant negative associations with both self‐ and partner‐reported relationship satisfaction, whereas the effects of self‐esteem were generally positive. In subsequent actor–partner interdependence mediation modeling (APIMeM), in which PD was used as the mediator, narcissism and self‐esteem continued to show differential relations to both the outcomes and the mediators. In particular, narcissism had positive actor effects on PD, which further negatively predicted both self‐ and partner‐reported relationship satisfaction. In contrast, the predictive effects of self‐esteem were reversed and weaker. Implications of the findings for research and practice are discussed.